2014
DOI: 10.1111/plb.12188
|View full text |Cite
|
Sign up to set email alerts
|

Linking waterlogging tolerance with Mn2+ toxicity: a case study for barley

Abstract: Vast agricultural areas are affected by flooding, causing up to 80% yield reduction and resulting in multibillion dollar losses. Up to now, the focus of plant breeders was predominantly on detrimental effects of anoxia, while other (potentially equally important) traits were essentially neglected; one of these is soil elemental toxicity. Excess water triggers a progressive decrease in soil redox potential, thus increasing the concentration of Mn(2+) that can be toxic to plants if above a specific threshold. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Since excessive accumulation of metal ions in plants is a possible factor in triggering ROS production , selecting waterlogging-tolerant genotypes can partially be achieved through plant tolerance to toxic Mn 2+ and Fe 2+ which often is increased in waterlogged soils (Khabaz-Saberi et al 2005). This is consistent with our recent study with the demonstration of a significant correlation between Mn 2+ tolerance and waterlogging tolerance in barley (Huang et al 2014). In the light of above, we believe that using activity of enzymatic AO as biochemical markers will not be able to discover QTLs conferring waterlogging stress tolerance in barley.…”
Section: Waterlogging Influence On Plants Growthsupporting
confidence: 89%
“…Since excessive accumulation of metal ions in plants is a possible factor in triggering ROS production , selecting waterlogging-tolerant genotypes can partially be achieved through plant tolerance to toxic Mn 2+ and Fe 2+ which often is increased in waterlogged soils (Khabaz-Saberi et al 2005). This is consistent with our recent study with the demonstration of a significant correlation between Mn 2+ tolerance and waterlogging tolerance in barley (Huang et al 2014). In the light of above, we believe that using activity of enzymatic AO as biochemical markers will not be able to discover QTLs conferring waterlogging stress tolerance in barley.…”
Section: Waterlogging Influence On Plants Growthsupporting
confidence: 89%
“…This variation could be harnessed to identify chromosomal regions not yet identified that are involved in Mn tolerance. Huang et al (2015) proposed that breeding for Mn tolerance could improve waterlogging tolerance in barley, which could be due to the decrease in soil redox potential under waterlogging, which in turn increases the soil Mn 2+ concentration and causes Mn-toxicity effects in plants. On the other hand, Leplat et al (2016) examined 248 barley varieties that were cultivated in six distinct environments prone to Mn deficiency, and identified several putative QTLs.…”
Section: Other Stressesmentioning
confidence: 99%
“…This may lead to morphological damage and increased susceptibility to pests and diseases (Catling, 1992;Greenway & Setter, 1996). Partial submergence, often referred to as waterlogging, leads to reduced gas diffusion, growth of microorganisms and production of toxic substances such as Fe 2+ , Mn 2+ and H 2 S (Huang et al, 2015;Setter et al, 2009). Whether it is partial and/or fully submerged conditions, there occurs a limited supply of O 2 a condition generally called hypoxia.…”
Section: Introduction: Plant's Association With Waterlogging and Submmentioning
confidence: 98%